Evaluation of the raw milk quality commercialized in Cornélio Procópio city, Paraná state. Commerce and consumption control - Beloti, Vanerli; Barros, Márcia de Aguiar Ferreira; Souza, Juliana Aparecida de; Nero, Luís Augusto; Santana, Elsa Helena Walter de; Balaria, Oscar; Curiaki, Yassuo (Semina: Ciências Agrárias, 1999)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The clandestine commerce of raw milk represents a important question of public health. With the objective to eradicate this commerce, to warn the population about the risks and to find solutions for the producers a campaign was achieved in the Cornélio Procópio City in the north of Parana' State .The advertising campaign "Pasteurized milk is health" was developed to stop the raw milk commerce, show its risks and how the producers could sell the product in the right ways and solve the problem. The advertising campaign involved public departments from the state and the city. The quality of the raw milk was firstly made, through 42 milk samples collect by the Cornélio Procópio Sanitary Vigilance from dairy producers. These samples were sent to the laboratory of Animal Products Inspection of Londrina State University where the physical-chemical and microbiological analysis were made. The analysis results indicated: all samples (100%) with unsatisfactory sedimentation; 21 (61,64%) with altered acidity; 18 (42,85%) with crioscopic points altered indicating addiction of water. Through the microbiological standard for type C milk (Brazilian Health Department, nÂ° 451, 19th September 1997), 25 (59,52%) samples were found with total mesophilic count above the acceptable, 42 (100%) with presence of total coliforms above 10 per ml and 34 (80,95%) with fecal conforms above 2 per ml. Finally, 2 (4,76%) samples were positives for the Ring-test. These results proved the low quality of the raw milk. According to the results, the public departments and the media developed the campaign in the following steps: I- Population and producers sensibility and results spread; II- Reunion with the Science and Biology teachers of the publics and privates schools: and III- Competition involving alt the students about the raw and the pasteurized milk. As a final result, the commerce of raw milk got down and a milk industry project will be implanted.